A Field Research on the Effect of Advertising Literacy Dimensions of Consumers to the Attitude for Rational and Emotional Ads - Becan, Cihan (Fırat University, 2022)
Advertising comes at the head of communication activities that brands have used to communicate with their consumers from past to present. The fact that advertising is seen as an indispensable element by brands can cause individuals to be consciously or unconsciously exposed to numerous messages in their daily life. In this regard, how consumers understand and interpret these messages can lead from the attitude towards the advertisement to the act of purchasing. At this point, advertising literacy has been playing an important role as a part of media literacy. The aim of this study is to determine the advertising literacy dimensions of consumers and to measure how their attitudes towards rational and emotional advertising change in terms of advertising literacy dimensions. For this purpose, the survey technique designed utilizing Google Forms has been applied to 271 people, on the scale of online networks with the convenience-sampling method. According to the results of the research, which was developed based on Malmelin's (2010) four-dimensional advertising literacy model, four basic advertising literacy factors were revealed: informational, rhetorical, visual/aesthetic and promotional. It has been observed that the informational and visual/aesthetic dimensions have a significant and positive effect on the attitude towards rational and emotional ads.

Markaların tüketicileri ile iletişime geçmek için geçmişten bu yana başvurdukları iletişim faaliyetlerinin başında reklam gelmektedir. Reklamın, markalar tarafından vazgeçilmez bir unsur olarak görülmesi, bireylerin gündelik hayatında bilinçli veya bilinçsiz bir şekilde sayısız mesajlara maruz kalmasına neden olmaktadır. Buna ilişkin olarak tüketicilerin bu mesajları nasıl anladığı ve yorumladığı, söz konusu reklama yönelik tutumdan, satın alma eylemine kadar yönlendirebilmektedir. Bu noktada medya okuryazarlığının bir parçası olarak reklam okuryazarlığı önemli bir rol oynamaktadır. Buradan hareketle çalışmada, tüketicilerin reklam okuryazarlık boyutları tespit edilerek, sahip oldukları reklam okuryazarlık boyutlarının rasyonel ve duygusal reklama yönelik tutumlarının ne yönde değiştiğini ölçümlemek amaçlanmaktadır. Bu amaçla elverişli örneklem yöntemiyle, çevrimiçi ortamda, 271 kişiye, Google Forms aracılığıyla oluşturulan anket tekniği uygulanmıştır. Malmelin’in (2010) dört boyutlu reklam okuryazarlığı modelinden hareketle geliştirilen araştırmanın sonucuna göre, bilgisel, retoriksel, görsel/estetik ve promosyonel olmak üzere dört temel reklam okuryazarlığı faktörü ortaya çıkarılmıştır. Rasyonel ve duygusal reklama yönelik tutum üzerinde, bilgisel ve görsel/estetik boyutun anlamlı ve pozitif yönde bir etkisi olduğu gözlemlenmiştir.
TÜKETİCİLERDEKİ REKLAM OKURYAZARLIĞI BOYUTLARININ RASYONEL VE DUYGUSAL REKLAMLARA YÖNELİK TUTUMA ETKİSİ ÜZERİNE BİR SAHA ARAŞTIRMASI